Alirocumab Has Greater Reduction of LDL-C Than Ezetimibe in Patients with Statin Intolerance - Nichols, Emma Hitt (MD Conference Express, 2014)
In clinical practice, up to 25% of patients are statin intolerant as a result of symptoms and abnormalities in biomarkers. This article discusses results from the Study of Alirocumab (REGN727/SAR236553) in Patients With Primary Hypercholesterolemia and Moderate, High, or Very High Cardiovascular Risk, Who Are Intolerant to Statins [Odyssey Alternative; NCT01709513]. These trials compared statin intolerant patients who were treated with alirocumab versus ezetimibe.